Are Family Support Correlated to Covid-19 Vaccination Acceptance in the Coastal Area of Indonesian? - Sumampouw, Oksfriani Jufri; Nelwan, Jeini Ester; Pinontoan, Odi Roni; Ticoalu, Jansje Vera (International Journal of Natural and Health Sciences, 2024)
Vaccination against COVID-19 is a global government program with the goals of reducing the spread of the virus, lowering the number of cases of COVID-19-related illnesses and deaths, and ultimately protecting communities from the disease so that they can continue to thrive socially and economically. A person's level of support from their family is one of the numerous aspects that affects their willingness to get a vaccine. In the island region of Indonesia, this study set out to examine the relationship between family support and the acceptance of the COVID-19 vaccine. The study in question is a correlational one. From February to July of 2022, researchers scoured Sangihe and Talaud Islands. Three hundred and fifty-nine adults (aged 18 and up) participated in the study. Support from family members and willingness to get a vaccine were the factors examined in this research. Specifically, a questionnaire is utilized. The chi-square test was used for bivariate data analysis. Respondents with strong family support are more likely to have accepted the COVID-19 vaccine in its entirety (88.7%), while those with weaker family support are more likely to have received the vaccine in its entirety (79.4%). A significant correlation between family support and acceptance of the COVID-19 vaccine was found, according to the results of the chi-squared test, with a significance level of 0.025 (< 0.05). It follows that having the support of one's family is a correlating factor to the acceptance of the COVID-19 vaccine